The Usefulness of Sexual Behaviour Assessment at the Beginning of Service to Predict the Suitability of Boars for Artificial Insemination - Stanisław Kondracki; Maria Iwanina; Anna Wysokińska; Dorota Banaszewska; Władysław Kordan; Leyland Fraser; Katarzyna Rymuza; Krzysztof Górski (Animals, 2021)
Parameters of sexual activity were determined in 49 young boars used for artificial insemination, four times at three-month intervals. The parameters included the time from entering the arena until mounting the phantom; the time from mounting the phantom until achieving erection; the time from achieving full erection until the start of ejaculation; duration of ejaculation; and the number of times the boar mounted the phantom. Characteristics of the ejaculates were also assessed. The libido parameter associated with the greatest efficacy of artificial insemination was the effectiveness of artificial insemination service, the time from entering the arena until the start of ejaculation. The significance of this trait for predicting ejaculation performance was analysed. The libido characteristics were classified into three categories: boars with a short reaction time to the phantom, boars with an intermediate reaction time, and boars with a long reaction time. For these groups, the characteristics of ejaculates collected at the start of the period during which ejaculates were collected and after three, six and nine months were determined. The sexual experience of boars was not associated with the expression of sexual behaviour because young boars during their first three months of ejaculate collections required less time to initiate ejaculation. The ejaculates with the greatest utility were obtained after six months of service. These ejaculates had the largest volume (255.22 mL), and the most insemination doses could be prepared from these ejaculates. On average, more than 23 insemination doses were prepared from ejaculates collected after six months of semen collections, which is about four doses more than from ejaculates collected at the start of artificial insemination service (p < 0.01).The time from entering the arena to beginning ejaculation can be used to predict a boar’s future libido. A relationship was shown between the level of libido and ejaculate characteristics. The ejaculates of the boars which needed the longest time to begin ejaculation at the start of semen collections had the greatest sperm concentration and number. In group 3, the boars’ejaculates contained about 6–9 × 109 more sperm than the ejaculates of boars from group 1. After six months of the experimental period, the difference was nearly 15 × 109 sperm (p < 0.05), and after nine months, it exceeded 22 × 109 sperm (p < 0.01).